An axiomatic study of Majority-rule (+ ) and associated consensus functions on hierarchies - Dong, Jianrong; Fernández-Baca, David; McMorris, F.R.; Powers, Robert C. (Discrete Applied Mathematics, 2011)
Consensus trees have been used routinely in systematic biology for over 30 years with the majority-rule consensus tree among the most popular. In this paper we give axioms that characterize a new consensus function, called majority-rule (+), that is based on a generalization of majority-rule to the supertree case. In addition, two other related consensus functions are characterized. ► The new majority-rule (+) consensus function on hierarchies is characterized. ► We present axioms that characterize the loose consensus function on hierarchies. ► The function that is the union of majority-rule and loose consensus is characterized.